Altering the Immunogenicity of Hemagglutinin Immunogens by Hyperglycosylation and Disulfide Stabilization - Thornlow, Dana N.; Macintyre, Andrew N.; Oguin, Thomas H.; Karlsson, Amelia B.; Stover, Erica L.; Lynch, Heather E.; Sempowski, Gregory D.; Schmidt, Aaron G. (Frontiers in Immunology, 2021)
Influenza virus alters glycosylation patterns on its surface exposed glycoproteins to evade host adaptive immune responses. The viral hemagglutinin (HA), in particular the H3 subtype, has increased its overall surface glycosylation since its introduction in 1968. We previously showed that modulating predicted N-linked glycosylation sites on H3 A/Hong Kong/1/1968 HA identified a novel, conserved epitope at the HA interface. This epitope is occluded on the native HA trimer but is likely exposed during HA “breathing” on the virion surface. Antibodies directed to this site are protective via an ADCC-mediated mechanism. This glycan engineering strategy made an otherwise subdominant epitope dominant in the murine model. Here, we asked whether cysteine stabilization of the hyperglycosylated HA trimer could reverse this immunodominance by preventing access to the interface epitope and focus responses to the HA receptor binding site (RBS). While analysis of serum responses from immunized mice did not show a redirection to the RBS, cysteine stabilization did result in an overall reduction in immunogenicity of the interface epitope. Thus, glycan engineering and cysteine stabilization are two strategies that can be used together to alter immunodominance patterns to HA. These results add to rational immunogen design approaches used to manipulate immune responses for the development of next-generation influenza vaccines.